Pelatihan Penulisan Artikel Ilmiah sebagai Upaya Meningkatan Kompetensi dan Keterampilan Publikasi bagi Mahasiswa - Suhadi, Agung; Afriyanto; Wadison, Epi (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Writing scientific articles is an essential competency for university students to support academic development, broaden scientific insight, and improve their ability to publish in national and international journals. However, many students still face challenges such as limited understanding of scientific article structures, academic writing techniques, citation and referencing practices, as well as the use of supporting tools such as Mendeley and similarity-checking applications. This community service activity aims to enhance the publication competence and skills of students at Universitas Muhammadiyah Bengkulu [English & Nursing Departments] through comprehensive scientific article writing training. The implementation methods include material presentation, hands-on IMRAD writing practice, guidance on using reference management applications, and Turnitin checking simulations. The results of the activity show a significant improvement in students’ understanding of writing techniques, completeness of article structure, and their ability to prepare manuscripts suitable for publication. Thus, this training is effective in improving students’ scientific publication competence and in supporting a productive academic culture within the university.